STUDI BIAYA PEMAKAIAN LISTRIK PADA GEDUNG C POLITEKNIK NEGERI MEDAN: STUDY OF THE COST OF ELECTRICITY CONSUMPTION IN BUILDING C OF THE MEDAN STATE POLYTECHNIC - Maulida, Quanita Aisyah; Gunoro; Cholish; Haq, Moh Zainul; Halomoan Sihite, Dery Matthew; Simanjutak, Petrus Hasiolan (Politeknik Negeri Medan, 2023)
Abstract Electrical energy has an important role in human life both in commercial activities and daily activities. The use of electricity can also be useful in tracing where and how much energy is used. This research aims to find out how much it costs to use electricity in the C building of the Medan State Polytechnic. Energy savings can be done by reducing energy consumption and use. The electric power installed at the Medan State Polytechnic is 1110 kVA. The total energy of building C for a month is 7494.6 kWh. The electricity bill at the Medan State Polytechnic Cbuilding is subject to a fine for using a power factor of less than 0.85, so the fine paid is Rp. 2,773,002. The total bill to be paid along with the fine is IDR 9,938,600. Keywords: Electrical Energi, Load, Consumption Abstrak Energi listrik mempunyai peranan penting dalam kehidupan manusia baik dalam kegiatan komersial maupun kegiatan sehari hari. Pemakaian listrik juga dapat berguna dalam menelusuri dimana dan berapa energi yang digunakan penelitian ini bertujuan untuk mengetahui berapa biaya pemakaian listrik pada gedung C Politeknik Negeri Medan. Penghematan energi dapat dilakukan dengan mengurangi konsumsi dan penggunaan energi. Daya listrik yang terpasang pada Politeknik Negeri medan sebesar 1110 kVA. Energi keseluruhan gedung C selama sebulan sebesar 7494,6 kWh. Tagihan listrik pada gedung C Politeknik Negeri Medan dikenakan denda karena pemakaian faktor daya kurang dari 0.85, jadi denda yang dibayar sebesar Rp 2.773.002. Total tagihan yang harus dibayar beserta dendanya sebesar Rp 9.938.600. Kata Kunci : Energi Listrik, Beban, Konsumsi